Estudos de liberação, permeação, adesão e estabilidade de membranas de gelatina contendo ácido úsnico na forma lipossomal para o tratamento de queimaduras - Lima, Bruno dos Santos (2017)
Burns are injuries in the skin that are usually caused by thermal accidents and the treatment of this disease is considered a great challenge due the amount of complications that are caused. Therefore, is necessary to look for alternatives that optimize the treatment of injuries caused by burns such as the use of bioactive membranes. Usnic acid (UA) is a substance that has potential for the burns treatment. However, this compound presents some unfavorable physical-chemical characteristics, such as low solubility in water. One way to stabilize this situation is through the use of AU encapsulated in liposome and combined with a gelatin membrane. Therefore, the purpose of this work was to prepare and characterize gelatin membranes containing AU incorporated in liposomes to the burns treatment. The membranes were prepared according with the casting method and the liposomes by the solvent rotavaporation technique. After obtaining, the swelling capacity of the membranes was evaluated. The analytical method was developed and validated by high performance liquid chromatography (HPLC), which was used to determine the content and encapsulation efficiency of UA in the membranes. In vitro release studies, permeation and adhesion of UA to skin layers were performed by Franz cells, and after, the stability and photostability of formulation was evaluated. Macroscopically, gelatin membranes showed yellowish color, smooth surface and swelling capacity in phosphate buffer (pH 7.4) and saline solution. The method developed by HPLC was effective to the identification and quantification of UA and all parameters used for validation showed suitable results according with the current legislation (RDC 899 – ANVISA, 2003). The UA content in the membranes was 172.07 ± 0.27 μg·cm-2, obtaining encapsulation efficiency of 93.75%. The in vitro release experiments demonstrated that the gelatin membranes containing UA in liposomes showed a controlled release profile, releasing 98.15% (41.37 μg·cm-2) of the UA in 24 hours of analysis. The UA has the ability to penetrate and permeate in the skin layers because it was quantified in the epidermis (3.54 ± 0.79 μg·cm-2) and dermis (13.64 ± 0.17 μg·cm-2) respectively, as well as, it has adhesion capacity, because it remained adhered to the skin after washing the formulation with saline solution (epidermis: 2.32 ± 0.95 μg·cm-2; dermis: 8.87 ± 0.56 μg·cm-2). The membranes showed stability to thermal variations and light exposure, because they didn’t show changes in the macroscopic characteristics and /or significant decrease in the UA content. According with the results obtained, we can conclude that gelatin membranes containing AU in liposomes are a promising formulation for the burns treatment, because they have the capacity to release control of UA and showed adequate stability, besides the fact that AU has the ability to penetrate, permeate and adhere in the skin layers.